Penguatan Institusi Lokal dan Menggerakkan Modal Sosial Melalui Komunitas Untuk Menciptakan Kampung Berdaya - Yuliyanti, Tri (JPAP: Jurnal Penelitian Administrasi Publik, 2018)
In carrying out its work a manager will use the concepts of management to facilitate the implementation of the task. By applying good public management practices and true, then the success of building a village will be realized. This research uses qualitative method by using the main instrument of Chairman of RW which is also Chairman of 3G Community. Some supporting instruments include observation and interview guidelines and secondary data. The conclusion of this research is to plan and implement environmental improvement in the region of Glintung, the Head of RW directly formed a community called "Community of 3G" (Glintung Go Green). With the Chairman of the RW who also served as Manager in the community, now the village of Glintung transformed into a powerless village. This condition is because the 3G community has good management and strategy and effective in supporting the success of the program. As an umbrella for the implementation of environmental improvement, the Community adopted the management of the company for the public sector. While the big strategy is the empowerment of citizens through 3G community. Where the strategy gives a lot of benefits in the form of livelihood of citizens and communities in the implementation of environmental improvement. Keywords: Community, Social Movement, Public Management, Local Institution